Rapid identification of all known retroviral reverse transcriptase sequences with a novel versatile detection assay - Seifarth, Wolfgang; Krause, Ulf; Hohenadl, Christine; Baust, Corinna; Hehlmann, Rüdiger; Leib-Mösch, Christine (Aids research and human retroviruses, 2000)
We have developed a highly sensitive, universal assay that allows detection as well as identification of all known retroviral reverse transcriptase (RT)-related nucleic acids in a biological sample by a single two-step experiment. The assay combines polymerase chain reaction (PCR) and reverse dot-blot hybridization (RDBH), using an array of immobilized synthetic retrovirus-specific oligonucleotides and two sets of mixed oligo primers (MOPs). These primers were derived from highly conserved motifs found in all known reverse transcriptase genes. The PCR/RDBH assay was used for qualitative analyses of human endogenous retrovirus (HERV) transcription in peripheral blood mononuclear cells (PBMCs) and in particles released by the human mammary carcinoma-derived cell line T47D. Sensitivity was further demonstrated by detection of down to 10 copies of pig endogenous retrovirus (PERV) DNA in human cDNA samples. Therefore, this assay is particularly useful for the identification of retroviral sequences in xenografts as well as in recipients of xenografted tissues and organs. Moreover, it is a valuable tool to detect retroviral transcripts and particles in cell cultures used for production of therapeutic polypeptides. The assay is further suitable for monitoring vector preparation used in human gene therapy to exclude transfer of copackaged endogenous retroviruses into target cells.
Elektronische Reproduktion der Druckausgabe
Gesehen am 19.05.2022